Enhancement of Interpretation and Inference Skills Through Guided Inquiry in Chemical Equilibrium - Fajar Wisnu Pambudi; Dian Novita (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
This research aims to know the improvement of students' interpretation and inference skills, which are drilled through a guided inquiry learning model on chemical equilibrium material at SMAN 1 Driyorejo. This research used one group pretest and posttest design with a sample of 35 students in class XI SMAN 1 Driyorejo Kabupaten Gresik. The research procedure consisted of 3 stages, namely the preparation stage in the form of pre-research data collection, the stage of carrying out data collection, and the final stage in the form of data analysis. The research instrument consisted of an observation sheet on the implementation of learning, an observation sheet of students' activity, and the question sheet of interpretation and inference skills test. Data collection methods consist of observing the implementation of learning, students' activities, and interpretation and inference skills tests. It can be concluded in this study that (1) the implementation of learning at the first meeting, the second meeting and the third meeting in the range of 85% - 92% with good criteria, (2) student activities during learning get results at the first meeting until the third meeting that is above 90% so that student activities support learning to practice students 'interpretation and inference skills (3) Students' interpretation and inference skills in the teaching and learning process have increased from pretest and posttest with N-gain values in the medium and high criteria.